STRUCTURAL EFFECTS OF GOLD NANOSPHERE COMPOSITE ON NONLINEAR ABSORPTION - Fitriana, Anna
Nonlinear electromagnetic wave response from matter has been an area of exciting research from more than half a century ago. This is due to the vast possibilities of applications of the resulted effects from a huge field enhancement to multistabilities. Here we report two kinds of third nonlinear optical processes, namely saturable absorption (SA) of which absorption goes to a saturation with increasing intensity, and the opposite, reverse saturable absorption (RSA). In SA process, the saturation of absorption is resulted from the depletion of ground state electrons due to excitation induced by the incoming light intensity, while the decay rate of these excited electrons is less than the excitation rate. On the other hand, in an RSA process, the excited state absorption is larger as compared to the ground state absorption at increased intensity, this is due to the two-photon absorption process. Conventionally, these two opposing processes are driven by incoming light intensity. In this study, by using quasistatic approximation we show that those processes can be driven by internal particle structure. Here we consider nonlinear absorption in a composite media consisting of a dilute mixture of identical coated nanospheres, gold core and dielectric shell and vice versa, in a dielectric background.